Effect of altitude and season on dry matter intake, THI and growth rate in mithun - R K CHAURASIA; A MECH; A DHALI; V K VIDYARTHI; C RAJKHOWA (Indian Journal of Animal Sciences, 2014)
A comparative study on effect of altitude and season on dry matter intake, THI and growth rate on growth performance and nutrient utilization in mithun calves was carried out at Medziphema farm (300 MSL) and Porba farm (2,100 MSL), Nagaland, India. The mithuns of either sex were selected and fed in confined condition. DM intake differed significantly during the seasons and between the altitudes. Growth rate of 521 g/day and 524 g/day were obtained during the experiment during pre- monsoon season which were nonsignificant. Growth rate of 643 g/ day and 548 g/day were obtained during winter at Medziphema and Porba farms, which were showing nonsignificant difference between body weights and at both altitudes. Feed conversion efficiency were nonsignificant between the altitudes and seasons. THI values differed significantly between the altitude and seasons. It was concluded that mithuns can be reared at both the altitudes without any significant difference in body weight.